“Nitelikli Televizyon”: Medya Profesyonellerinin Perspektifinden Türk Televizyon Dizilerinde Nitelik - TÜZÜN ATEŞALP, SELİN (My University, 2016)
With the development of television sector in parallel to advertisement and cinema sector in Turkey, the television dramas have improved significantly in terms of quality and quantity starting with late 1990s. With the impact of substantial demand from the audience for local dramas, the investments for TV drama series increase. The units within TV channels which are responsible for dramas and the professionals that act as the gatekeepers in these units make strategic decisions on the projects to be realized. The “symbol creators” who are involved in different stages of the production process make decisions within creative process that have an impact on the quality of the outcome in spite of all limitations of the industry motivated by profit. Which factors make television dramas appealing for the channels in Turkey? What kind of criteria do the channels consider when assessing the television drama projects? Does quality guarantee high ratings? Which factors play a negative role on the quality of television dramas? This article aims to explore the professionals’ assessment of quality in television dramas within the framework of these questions based on in depth interviews’ data

Avec le développement du secteur de la télévision parallèlement au secteur de la publicité et du cinéma en Turquie, les drames télévisés se sont considérablement améliorés en termes de qualité et de quantité à partir de la fin des années 1990. L’investissement dans les séries s’accroit sous l’influence de l’intérêt que portent les spectateurs aux drames nationaux. Les unités au sein des chaînes de télévision qui sont responsables de drames et les professionnels qui y agissent en tant que “gardiens” prennent des décisions stratégiques sur les projets à réaliser. Et les « créateurs symboliques » prennent des décisions influençant la qualité du travail lors de la création malgré les restrictions de l’industrie qui agit au nom du profit. Quels sont les facteurs, en Turquie, qui rendent les séries télévisées attractifs ? Quels sont les critères dont tiennent compte les chaînes de télévision en évaluant les projets? La qualité amène-t-elle d’office une forte audience? Quels sont les facteurs qui agissent de façon négative sur la qualité des séries? Cet article a pour but d’explorer l’évaluation des professionnels de la qualité des séries télévisées, à partir des entretiens approfondis.

Türkiye’de televizyon sektörünün reklam ve sinema sektöründeki gelişmelere paralel olarak gelişmesiyle, özellikle 1990’lı yılların sonlarından itibaren televizyon dizileri* nitelik ve nicelik açısından kayda değer bir gelişme göstermeye başlar. İzleyicilerin yerli dramalara gösterdiği yoğun ilginin de etkisiyle dizilere yapılan yatırımlar artar. Televizyon kanallarının dramalardan sorumlu birimleri ve bu birimlerde çalışan “eşik bekçisi” konumundaki profesyoneller, hangi projelerin hayata geçirilip hangilerinin geçirilmeyeceğine dair stratejik kararlar vermektedirler. Üretim sürecinin farklı aşamalarında yer alan “sembol yaratıcıları” ise kâr motivasyonu ile hareket eden endüstrinin tüm sınırlamalarına rağmen, yaratıcı süreçte ortaya çıkan işin niteliğini etkileyecek kararlar vermektedirler. Türkiye’de dizileri kanallar için çekici kılan faktörler nelerdir? Kanallar dizi projelerini değerlendirirken hangi ölçütleri dikkate almaktadır? Nitelik beraberinde yüksek izlenme oranlarını getirir mi? Televizyon dizilerinin niteliği üzerinde olumsuz rol oynayan faktörler nelerdir? Bu çalışmada, bu sorular çerçevesinde derinlemesine görüşmelerden elde edilen verilere dayanarak profesyonellerin televizyon dizilerinde niteliğe dair değerlendirmeleri ele alınacaktır.
“Quality TV”: Quality in Turkish Television Dramas from the Perspective of Media Professionals
“Une télévision de qualité”: La qualité des séries télévisées turques du point de vue des professionnels des médias
Keywords: Turkish television drama sector; Turkish television drama series; “quality television”; television; le secteur des drames télévisés turques; les séries télévisées turques; la télévision de qualité; la télévision; Türk dizi sektörü; diziler; “nitelikli televizyon”; televizyon